Determinants of Tax Non-Compliance among Small and Medium Enterprises in Zimbabwe - Dlamini, Banele (Journal of Economics and Behavioral Studies, 2017)
Small and medium-scale enterprises (SMEs) are recognized global for being the backbone of the economy through; economic advancement; innovation, wealth generation and furthering growth. SMEs have a high tax non compliance rate which hinders the development they bring to many economies. This paper aims to establish the major determinants of tax non-compliance among SMEs in the Zimbabwean economy. The survey research design was used and the SMEs operating in the Bulawayo provincewere considered as the sample of the study. The stratified random sampling technique was adopted in eliciting information and questionnaires were administered in the collection of data from the respondents. 187 questionnaires were issued out and 150 were returned. Regression analysis was used to establish the relationship that exists between tax non-compliance and the predictive variables, using SPSS ver. 22. The study revealed that poor follow-up strategy and lack of a tax audit, high tax rates, financial constraints, abuse of public funds by authorities and tax education as the major determinants. SME operators should apply modern business survival strategies so as to counter financial constraints. ZIMRA should maintain a database for SMEs for tax audit purposes; intensify follow-up strategies, increase tax audits and increase tax support services to SMEs. The government should consider reducing tax rates (which are perceived to be too high) as they promote tax evasion and failure among SMEs.